Solvatochromism and potentiometic studies of some active nitroso- and nitroso-azo- compounds - Masoud, Mamdouh Saad; Khalil, Ekram Abd El-Moniem; El Enein, Saeda Abou El-Thana Abou; Kamel, Hesham Mostafa (European Journal of Chemistry, 2011)
The stability studies of biologically active 2,4-dinitrosoresorcinol, o-carboxy phenylazo-dinitrosoresorcinol, N,N`-bis-[4,4`-(1,3-diphenyltriazine)]-diacetamide, 2-amino-6-phenylazo-pyridin-3-ol, 2-amino-3-hydroxy-pyridin-6-ylazo)-benzoic acid, 4-(2-amino-3-hydroxy-pyridin-6-ylazo)-benzoic acid ethyl ester and N-[4-(2-amino-3-hydroxy-pyridin-6-ylazo)-phenyl]-acetamide compounds were studied. The dissociation constants were determined potentiometrically. The thermodynamic parameters of dissociation were evaluated. Regression analysis is applied for correlating the different parameters. The results help to assign the solute-solvent interactions and the solvatochromic potential of the investigated compounds. The electronic character of the substituent and the chemical nature of the solvent are major factors for the observed solvatochromism.